2019
DOI: 10.1017/s0144686x19000187
|View full text |Cite
|
Sign up to set email alerts
|

Assisted living facilities as sites of encounter: implications for older adults’ experiences of inclusion and exclusion

Abstract: Most of the existing literature on inclusion and exclusion among older adults focuses on community-dwelling individuals. In this article, we draw on the results of a comparative case study to explore how older adults in two assisted living settings experience inclusion and exclusion. One site was a low-income facility and the other a higher-end facility in a mid-sized Canadian city. Bridging together geographies of encounter and gerontological approaches on social inclusion, we analyse interviews with tenants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Additionally, mismatches in cognitive health led to feelings of isolation as those in good health felt isolated when surrounded by those with lower communication abilities. The issues of random meal seating and lack of transportation leading to feelings of social exclusion align with previous research which found the structure of ALFs can moderate feelings of isolation (Herron et al ., 2020). The current study highlights how both resident health and the structure of ALFs can interact in ways that propagate feelings of loneliness.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, mismatches in cognitive health led to feelings of isolation as those in good health felt isolated when surrounded by those with lower communication abilities. The issues of random meal seating and lack of transportation leading to feelings of social exclusion align with previous research which found the structure of ALFs can moderate feelings of isolation (Herron et al ., 2020). The current study highlights how both resident health and the structure of ALFs can interact in ways that propagate feelings of loneliness.…”
Section: Discussionmentioning
confidence: 99%
“…Although researchers have argued that the number of ties between individuals who make up the social network in CCRCs is quite sparse, with most residents not even knowing each other [14], others have shown that the CCRC is effective in alleviating loneliness and facilitating social connections among its residents [15, 16]. However, some research has stressed the presence of cliques, conflicts, and loneliness in residential care settings [17, 18]. Moreover, a recent review of the literature has concluded that the rates of loneliness in long-term care are high, with more than 50% of the residents reporting loneliness [19].…”
Section: Introductionmentioning
confidence: 99%
“…These challenges limit their geographical space and shrink their social circles, making them more dependent on their immediate surroundings and family or community support for social inclusion. Loss of and dismissal of previous social roles and identities can also deteriorate a sense of valued social self, as they are reduced to being merely 'care recipients' or 'old' (Burns et al, 2012;Herron et al, 2020). Older adults do not necessarily need to perceive shrinking social networks and 'aloneness' in a negative way.…”
mentioning
confidence: 99%